ONOMASTIC SPACE OF THE SHORT STORIES COLLECTION “SELO ZA VIJNY” OF MARKO CHEREMSHYNA - Liakh, T. O.; Grechyn, I. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The onomastic space is an important component of the world’s picture of the artistic text, it reflects the individual manner of the writer and the cultural and historical period. Marko Cheremshyna is a writer who lived and worked during the formation of Ukrainian modernism, so the research of the onomastic space of the writer’s works requires detailed study. Different views have been formed in relation to the concept of the onomastic space in modern Ukrainian linguistics. The statements of L. Beley, V. Kalinkin, Yu. Karpenko, especially their approach to the study of the onomastic space in an artistic text, terminology for the designation of proper names in an artistic work are relevant for the proposed study. We also use the statements of those linguists who consider the onomastic space in connection with the worldview of the author (N. Podolska, L. Seliverstova). Approach to classification of the onomastic space of Marko Cheremshyna’s short story collection “Selo za vijny” (“Village during the War”) is based on the distribution of proper names of living beings and names of inanimate objects. The linguistic method of research is descriptive. The units of analysis were selected according to this method, classification and interpretation of the onyms was carried out using the techniques of external and internal interpretation. It was concluded that the types of onyms in Marko Cheremshyna’s collection “Selo za vijny” are subject to the genre of the artistic text, its general idea. It has been found that the onymic space of this collection is represented in quite a variety of ways, but the largest group in the collection is made up of anthroponyms. The onomastic space of Marko Cheremshyna’s short story collection “Selo za vijny” has a significant artistic value and expresses the individual style of the writer.